Metode Keteladanan dalam Pendidikan Islam - Nurul Hidayat (Ta'allum: Jurnal Pendidikan Islam, 2015)
In achieving the target of national education, formal or non-formal, the role of a teacher is vital. Of the roles to be played by the teacher, providing good model for the students is seen as effective and efficient. In this case, the students would see not only how to develop their cognitive aspect but also affective and psychomotor aspects. To be specific with Islamic education, providing good model is effective in internalizing Islamic values to the students.